Four‐Dimensional Paleomagnetic Dataset: Plio‐Pleistocene Paleodirection and Paleointensity Results From the Erebus Volcanic Province, Antarctica (Dataset) ... - Asefaw, H.; L. Tauxe; Koppers, A. A. P.; H. Staudigel (Magnetics Information Consortium (MagIC), 2022)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Four‐Dimensional Paleomagnetic Dataset: Plio‐Pleistocene Paleodirection and Paleointensity Results From the Erebus Volcanic Province, Antarctica ...